Spatial choice is biased by chemical cues from conspecifics in the speckeled worm eel Myrophis punctatus - Rodrigo Egydio Barreto; Maria Fernanda Coelho Junqueira; Tan Tjui-Yeuw; Gilson Luiz Volpato (Neotropical Ichthyology, 2010)
The speckeld worm eel Myrophis punctatus lives in high-densities assemblages, and usually digs through, or lies on the substrate. These behaviours could lead to chemical marks on the substrate and could modulate the spatial distribution in this species. We tested the hypothesis that the spatial choice of the speckled worm eel is modulated by the presence of conspecific odour on the substrate. Here, we showed that the speckled worm eel avoids the substrate area containing the conspecific odour, indicating that this chemical cue modulates the eel's spatial decision. The eels clearly detected the conspecific's odour. This perception might indicate the presence of conspecifics into the substrate. Since the eels avoided an area containing conspecific odour, we suggest this may be a response that avoids the consequences of invading a resident-animal's territory. A enguia mirongo-mirim Myrophis punctatus vive em agrupamentos de alta densidade populacional e comumente se enterra ou permanece sob o substrato. Esses comportamentos podem levar a marcas químicas no subtrato e podem, portanto, modular o uso do espaço nessa espécie. Neste estudo, testamos a hipótese de que a preferência espacial da enguia mirongo-mirim é influenciada pela presença de odor do animal coespecífico no subtrato. Mostramos que as enguias evitam a área que contém tal odor, indicando que as decisões de ocupação espacial podem ser influenciadas por pistas químicas de coespecíficos. As enguias claramente detectaram o odor de um animal coespecífico e essa percepção poderia ser um indicativo da presença de um coespecífico enterrado no substrato. Visto que elas evitam uma área contendo tal odor, sugerimos que isso poderia ser uma resposta para evitar invadir o território de um animal residente.